Opportunities and Challenges of Li2C4O4 as Pre‐Lithiation Additive for the Positive Electrode in NMC622||Silicon/Graphite Lithium Ion Cells. Issue 24 (7th July 2022) - Gomez‐Martin, Aurora; Gnutzmann, Maike Michelle; Adhitama, Egy; Frankenstein, Lars; Heidrich, Bastian; Winter, Martin; Placke, Tobias
Abstract: Silicon (Si)‐based negative electrodes have attracted much attention to increase the energy density of lithium ion batteries (LIBs) but suffer from severe volume changes, leading to continuous re‐formation of the solid electrolyte interphase and consumption of active lithium. The pre‐lithiation approach with the help of positive electrode additives has emerged as a highly appealing strategy to decrease the loss of active lithium in Si‐based LIB full‐cells and enable their practical implementation. Here, the use of lithium squarate (Li2 C4 O4 ) as low‐cost and air‐stable pre‐lithiation additive for a LiNi0.6 Mn0.2 Co0.2 O2 (NMC622)‐based positive electrode is investigated. The effect of additive oxidation on the electrode morphology and cell electrochemical properties is systematically evaluated. An increase in cycle life of NMC622||Si/graphite full‐cells is reported, which grows linearly with the initial amount of Li2 C4 O4, due to the extra Li + ions provided by the additive in the first charge. Post mortem investigations of the cathode electrolyte interphase also reveal significant compositional changes and an increased occurrence of carbonates and oxidized carbon species. This study not only demonstrates the advantages of this pre‐lithiation approach but also features potential limitations for its practical application arising from the emerging porosity and gas development during decomposition of the pre‐lithiation additive. Abstract : Pre‐lithiation is a promising approach to compensate for active lithium losses in lithium ion battery cells. Herein, the beneficial impact of Li2 C4 O4 as pre‐lithiation additive on prolonging the cycle life of NMC622||Si/graphite full‐cells is reported. This study also points out possible detrimental effects of decomposition products such as releasing gases and remaining cathode porosity on cell performance.